Dynamics of the Ecological Agroalimentary Produce Market - Cornelia Petroman; Ioan Petroman; Gabriela Ivașcu; Diana Marin; Ștefan Coman; Moisina Șucan (Scientific Papers Animal Science and Biotechnologies, 2023)
The market of ecological agroalimentary produce in Romania tends to have a positive evolution, identical with the world market, according to the specialists in the field. The market of ecological produce in Romania is being developed: from the point of view of its life cycle, it is steadily going to the growth period. Since the appearance period passed away, now there is the unsatisfied need of green produce: the first producers able to meet this need have appeared and they have started to meet the needs related to these produce.